Three-dimensional hard carbon matrix for sodium-ion battery anode with superior-rate performance and ultralong cycle life. Issue 46 (26th October 2015) - Yuan, Zhengqiu; Si, Lulu; Zhu, Xiaobo
Abstract : A three-dimensional (3D) hard carbon matrix (3DHCM) derived from sodium polyacrylate precursor was achieved, delivering a superior-rate performance and ultralong cycle life performance, and sodium-ion full cell properties. Abstract : Taking advantage of sodium polyacrylate, composed of interlaced carbon chains and inorganic functional groups (–COONa) uniformly grafted onto the carbon chains, a three-dimensional hard carbon matrix (3DHCM) has been obtained. The resultant material is composed of three-dimensional macroporous interconnected networks of carbon nanosheets (thickness, 5–30 nm). The 3DHCM has been studied as an anode material for sodium-ion batteries. The unique three-dimensional porous structure results in a high initial charge capacity of 341 mA h g −1, stable cycling capacity of 232.8 mA h g −1 (after 100 cycles, 50 mA g −1 ), superior-rate performance (stable capacities of 210, 197, 128 and 112 mA h g −1 at 200, 500, 5000, 8000 mA g −1, respectively) and ultralong cycle life (116 mA h g −1 at 4 A g −1 after 3000 cycles). At the same time, an increase in the trend of the sloping capacity percentage at total discharge is observed. More obvious "graphitic" domains with larger interplanar spacing (∼0.46 nm) were produced in the electrochemical cycles and detected using ex situ HRTEM, further confirming that the first higher-voltage region (above 0.1 V) should be attributed to the sodium insertion between the parallel graphene layers in the hard carbon. We also find that the electrolyte (1 M NaClO4 in PC) severely decomposes at the electrode/electrolyte interface during deep electrochemical cycles (6000 cycles), resulting in the deterioration of the electrode and fast capacity fading. Furthermore, a room-temperature sodium-ion full cell was constructed using 3DHCM as an anode and Na3 V2 (PO4 )3 /C as a cathode, (−) 3DHCM‖1 M NaClO4 in PC‖Na3 V2 (PO4 )3 /C (+), delivering a discharge capacity of 90 mA h g −1 at a current density of 500 mA g −1 . We believe that our findings will be helpful in speeding up the development of room-temperature high-rate, long life and low cost sodium-ion batteries for large-scale energy storage systems, and even as alternatives to lithium-ion batteries.